p21-Activated Kinase 1 Is Permissive for the Skeletal Muscle Hypertrophy Induced by Myostatin Inhibition - Barbé, Caroline; Loumaye, Audrey; Lause, Pascale; Ritvos, Olli; Thissen, Jean-Paul (Frontiers in Physiology, 2021)
Skeletal muscle, the most abundant tissue in the body, plays vital roles in locomotion and metabolism. Understanding the cellular processes that govern regulation of muscle mass and function represents an essential step in the development of therapeutic strategies for muscular disorders. Myostatin, a member of the TGF-β family, has been identified as a negative regulator of muscle development. Indeed, its inhibition induces an extensive skeletal muscle hypertrophy requiring the activation of Smad 1/5/8 and the Insulin/IGF-I signaling pathway, but whether other molecular mechanisms are involved in this process remains to be determined. Using transcriptomic data from various Myostatin inhibition models, we identified Pak1 as a potential mediator of Myostatin action on skeletal muscle mass. Our results show that muscle Pak1 levels are systematically increased in response to Myostatin inhibition, parallel to skeletal muscle mass, regardless of the Myostatin inhibition model. Using Pak1 knockout mice, we investigated the role of Pak1 in the skeletal muscle hypertrophy induced by different approaches of Myostatin inhibition. Our findings show that Pak1 deletion does not impede the skeletal muscle hypertrophy magnitude in response to Myostatin inhibition. Therefore, Pak1 is permissive for the skeletal muscle mass increase caused by Myostatin inhibition.